Optimisation of recovery protocols for double-base smokeless powder residues analysed by total vaporisation (TV) SPME/GC-MS - Sauzier, Georgina; Bors, D.; Ash, J.; Goodpaster, J.; Lewis, Simon (Elsevier, 2016)
The investigation of explosive events requires appropriate evidential protocols to recover and preserve residues from the scene. In this study, a central composite design was used to determine statistically validated optimum recovery parameters for double-base smokeless powder residues on steel, analysed using total vaporisation (TV) SPME/GC-MS. It was found that maximum recovery was obtained using isopropanol-wetted swabs stored under refrigerated conditions, then extracted for 15 min into acetone on the same day as sample collection. These parameters were applied to the recovery of post-blast residues deposited on steel witness surfaces following a PVC pipe bomb detonation, resulting in detection of all target components across the majority of samples. Higher overall recoveries were obtained from plates facing the sides of the device, consistent with the point of first failure occurring in the pipe body as observed in previous studies. The methodology employed here may be readily applied to a variety of other explosive compounds, and thus assist in establishing ‘best practice’ procedures for explosive investigations.